Nèstor Luján e Joan Perucho, 'gastrófogos' al servizio della serenissima: racconti di cibi e spezie sulle rotte del Mediterraneo d'Oriente. - CAROL GERONÈS, LÍDIA (Scripta)
Using a transversal approach, this article analyses some of the first texts on gastronomy by Nèstor Luján and Joan Perucho, which appeared in the magazine Destino, in which, although with different intentions, the two authors write about food and the exchange of foods in Mediterranean cuisine, with special attention to a possible dialogue with the Italian territory, mainly observing the case of Venice, considered the gateway to the East and an urban unicum on the Levantine and Byzantine Mediterranean routes.